Numaswitch, a biochemical platform for the efficient production of disulfide-rich pepteins - Nguyen, Bach-Ngan; Tieves, Florian; Neusius, Florian G.; Götzke, Hansjörg; Schmitt, Lutz; Schwarz, Christian (Frontiers in Drug Discovery, 2023)
The application of long-chained peptides (+30 aa) and relatively short proteins (<300 aa) has experienced an increasing interest in recent years. However, a reliable production platform is still missing since manufacturing is challenged by inherent problems such as mis-folding, aggregation, and low production yields. And neither chemical synthesis nor available recombinant approaches are effective and efficient. This in particular holds true for disulfide-rich targets where the correct isomer needs to be formed. With the technology Numaswitch, we have now developed a biochemical tool that circumvents existing limitations and serves as first production platform for pepteins, hard-to-be-produced peptides and proteins between 30 and 300 amino acids in length, including disulfide-rich candidates. Numaswitch is based on bifunctional Switchtag proteins that force the high-titer expression of pure inclusion bodies and simultaneously assist in the efficient refolding of pepteins into functional pepteins. Here, we demonstrate the successful application of the Numaswitch platform for disulfide-containing pepteins, such as an antimicrobial fusion peptide, a single-chain variable fragment (scFv), a camelid heavy chain antibody fragment (VHH) and the human epidermal growth factor.